When ecosystems and their services are not co-located: oceans and coasts. (15th March 2017) - Drakou, Evangelia G.; Pendleton, Linwood; Effron, Micah; Ingram, Jane Carter; Teneva, Lida
Abstract: Local, regional, and global policies to manage protect and restore our oceans and coasts call for the inclusion of ecosystem services (ES) in policy-relevant research. Marine and coastal ES and the associated benefits to humans are usually assessed, quantified, and mapped at the ecosystem level to inform policy and decision-making. Yet those benefits may reach humans beyond the provisioning ecosystem, at the regional or even global level. Current efforts to map ES generated by a single ecosystem rarely consider the distribution of benefits beyond the ecosystem itself, especially at the regional or global level. In this article, we elaborate on the concept of "extra-local" ES to refer to those ES generating benefits that are enjoyed far from the providing ecosystem, focusing on the marine environment. We emphasize the spatial dimension of the different components of the ES provision framework and apply the proposed conceptual framework to food provision and climate regulation ES provided by marine and coastal ecosystems. We present the different extents of the mapping outputs generated by the ecosystem-based vs. the extra-local mapping approach and discuss practical and conceptual challenges of the approach. Lack of relevant ES mapping methodologies and lack of data appeared to be the most crucial bottlenecks in applying the extra-local approach for marine and coastal ES. We urge for more applications of the proposed framework that can improve marine and coastal ES assessments help fill in data gaps and generate more robust data. Such assessments could better inform marine and coastal policies, especially those linked to equal attribution of benefits, compensation schemes and poverty alleviation.